The Transfer of the Ferredoxin Gene From the Chloroplast to the Nuclear Genome Is Ancient Within the Paraphyletic Genus Thalassiosira - Roy, Alexandra-Sophie; Woehle, Christian; LaRoche, Julie (Frontiers in Microbiology, 2020)
Ferredoxins are iron-sulfur proteins essential for a wide-range of organisms because they are electron transfer mediator involved in multiple metabolic pathways. In phytoplankton, these proteins are active in the mature chloroplasts but the petF gene, encoding for ferredoxin, has been found either in the chloroplast genome or transferred to the nuclear genome as observed in the green algae and higher plant lineage. We experimentally determined the location of the petF gene in 12 strains of Thalassiosira covering three species using DNA sequencing and qPCR assays. The results showed that petF gene is located in the nuclear genome of all confirmed T. oceanica strains (CCMP0999, 1001, 1005, 1006) tested. In contrast, all T. pseudonana (CCMP1012, 1013, 1014, 1335) and T. weissflogii (CCMP1010, 1049, 1052) strains studied retained the gene in the chloroplast genome, as generally observed for Bacillariophyceae. Our evolutionary analyses further extend the dataset on the localization of the petF gene in the Thalassiosirales. The realization that the petF gene is nuclear-encoded in the Skeletonema genus allowed us to trace the petF gene transfer back to a single event that occurred within the paraphyletic genus Thalassiosira. Phylogenetic analyses revealed the need to reassess the taxonomic assignment of the Thalassiosira strain CCMP1616, since the genes used in our study did not cluster within the T. oceanica lineage. Our results suggest that this strains’ diversification occurred prior to the ferredoxin gene transfer event. The functional transfer of petF genes provides insight into the evolutionary processes leading to chloroplast genome reduction and suggests ecological adaptation as a driving force for such chloroplast to nuclear gene transfer.